When supply meets demand: wage inequality in Portugal - Mário Centeno; Álvaro A. Novo (Institute for the Study of Labor (IZA), 2009)
Wage inequality in Portugal increased over the last quarter of century. The period from 1982 to 1995 witnessed strong increases in both upper- and lower-tail inequality. A shortage of skills combined with skill-biased technological changes are at the core of this evolution. Since 1995, lower-tail inequality decreased, while upper-tail inequality increased at a slower rate. The supply of high-skilled workers more than doubled during this period, contributing significantly to the slowdown. Polarization of employment demand is the more credible explanation for the more recent evolution. As in other developed economies, for instance Germany and the United States, we show that institutions played a minor role in shaping changes in inequality.
Keywords: J3; D3; O3; 330; Inequality; polarization; supply; demand; institutions; Lohnstruktur; Arbeitsnachfrage; Arbeitsangebot; Qualifikation; Technischer Fortschritt; Institutionalismus; Portugal